Transformasi Karakter Don dalam Film Jumbo: Analisis Character Arc berdasarkan Teori K.M. Weiland - Daffa Nashwan Rabbanee, Muhammad; Ikhsan, Ibrahim (CENDEKIA: Jurnal Ilmu Sosial, Bahasa dan Pendidikan, 2026)
This study aims to analyze the transformation of Don’s character in the film Jumbo using K.M. Weiland’s character arc framework. The research employs a qualitative method with a descriptive-interpretative approach. Data were collected through repeated viewing of selected scenes that represent character development, and analyzed based on narrative structure, including exposition, inciting incident, rising conflict, climax, and resolution, as well as supported by visual elements such as facial expressions, gestures, and cinematic composition. The findings reveal that Don’s character undergoes a dynamic and gradual transformation. Initially, he is driven by a strong need for social validation, which develops into a negative change arc as he reinforces false beliefs and exhibits increasingly egoistic behavior. At the climax, Don reaches a critical turning point that triggers self-reflection. Ultimately, he transitions into a positive change arc, demonstrated through empathy, responsibility, and concern for others. This study highlights that character development in film is constructed through the interplay of conflict, social relationships, and a structured narrative process.